Specific binding of urinary-type plasminogen activator (u-PA) to vitronectin and its role in mediating u-PA-dependent adhesion of U937 cells. - Moser, T L (1995)
The present paper described interactions of urinary-type plasminogen activator (u-PA) with isolated protein components of the extracellular matrix (ECM) using kinetic and ligand-blotting analyses, as well as adhesion studies with u-PA-saturated U937 monocytic cells. Kinetic analyses showed that fibronectin and laminin were moderately effective at decreasing activation of plasminogen by u-PA (3-4-fold decrease in kcat/Km), while activation was stimulated slightly by collagen types I and IV (2-4-fold increase in kcat/Km). Ligand-blotting experiments using intact immobilized ECM proteins demonstrated that u-PA binds predominantly to vitronectin. This was supported by ELISA studies, which showed concentration dependent, saturable, reversible binding of u-PA to vitronectin (Kd,app. of 97 nM). Limited proteolysis of vitronectin followed by ligand-blotting analysis demonstrated u-PA binding to a specific vitronectin fragment (M(r) 49,000), and binding was shown to occur through the N-terminal fragment of u-PA. N-terminal sequence analysis indicated that this binding fragment of vitronectin originates with Thr-122 and comprises the hemopexin domain, including the heparin-binding region of the vitronectin molecule. Plasminogen activator inhibitor type I did not compete with u-PA for binding to vitronectin, suggesting both molecules may co-localize on vitronectin. In contrast, binding of u-PA to vitronectin was significantly inhibited by plasminogen, suggesting these molecules share a common binding site on vitronectin. In addition to in vitro studies, experiments were performed to assess the contribution of direct binding of u-PA to vitronectin on the adhesive behaviour of U937 cells. Binding of u-PA-saturated U937 cells to vitronectin was inhibited 66% by excess vitronectin, suggesting that direct binding of u-PA to vitronectin is the mechanism by which u-PA-dependent adhesion of U937 cells to vitronectin is mediated.